Answer

Verified

305.4k+ views

**Hint:**For solving this question you should know about the general form of trigonometric functions. In this problem we will solve it with the help of a right triangle and applying Pythagoras Theorem on that. That will provide us with the final answer and here we can consider the value of $\theta $ as 2.

**Complete step by step answer:**

According to our question it is asked of us to prove that ${{\sin }^{2}}2+{{\cos }^{2}}2=1$. Here we can see that this is given in a form of ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$. So, here we can consider the value of $\theta $ as 2. So, now our question is to prove, ${{\sin }^{2}}2+{{\cos }^{2}}2=1$. For this we will use a right triangle. And then we will apply Pythagoras Theorem for proving this and we will also keep in mind that $\dfrac{P}{H}=\sin \theta $ and $\dfrac{B}{H}=\cos \theta $. Here P stands for perpendicular, H stands for hypotenuse and B stands for base. Now if we make a right triangle as follows,

Now, let angle A be $\theta $. We will apply the theorem of Pythagoras Theorem, that is, ${{a}^{2}}+{{b}^{2}}={{c}^{2}}$, where a is the value of perpendicular, b is the value of base and c is the value of hypotenuse. So, we will get it as,

$\begin{align}

& \text{perpendicula}{{\text{r}}^{2}}+\text{bas}{{\text{e}}^{2}}=\text{hypotenus}{{\text{e}}^{2}} \\

& \Rightarrow AB{{}^{2}}+B{{C}^{2}}=A{{C}^{2}} \\

\end{align}$

Dividing the above equation by $A{{C}^{2}}$, we will get,

$\begin{align}

& \dfrac{A{{B}^{2}}+B{{C}^{2}}}{A{{C}^{2}}}=\dfrac{A{{C}^{2}}}{A{{C}^{2}}} \\

& \Rightarrow \dfrac{A{{B}^{2}}}{A{{C}^{2}}}+\dfrac{B{{C}^{2}}}{A{{C}^{2}}}=1 \\

\end{align}$

We know that,

$\dfrac{P}{H}=\sin \theta $

$\dfrac{B}{H}=\cos \theta $

Now in the equation, $\dfrac{A{{B}^{2}}}{A{{C}^{2}}}+\dfrac{B{{C}^{2}}}{A{{C}^{2}}}=1$,

$\Rightarrow \dfrac{AB}{AC}=\sin \theta ,\dfrac{BC}{AC}=\cos \theta $

Thus we get the conclusion that,

${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$

And as we have assumed that $\theta =2$,

So, ${{\sin }^{2}}2+{{\cos }^{2}}2=1$.

Hence it is proved.

**Note:**Pythagoras Theorem, that is, $\text{perpendicula}{{\text{r}}^{2}}+\text{bas}{{\text{e}}^{2}}=\text{hypotenus}{{\text{e}}^{2}}$ is used in this question is the most basic theorem in mathematics and to be used in most questions like this with right angled triangles. Do not forget that, $\dfrac{P}{H}=\sin \theta ,\dfrac{B}{H}=\cos \theta ,\dfrac{P}{B}=\tan \theta $.

Recently Updated Pages

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

How do you arrange NH4 + BF3 H2O C2H2 in increasing class 11 chemistry CBSE

Is H mCT and q mCT the same thing If so which is more class 11 chemistry CBSE

What are the possible quantum number for the last outermost class 11 chemistry CBSE

Is C2 paramagnetic or diamagnetic class 11 chemistry CBSE

What happens when entropy reaches maximum class 11 chemistry JEE_Main

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Explain why a There is no atmosphere on the moon b class 11 physics CBSE

Difference Between Plant Cell and Animal Cell

Can anyone list 10 advantages and disadvantages of friction

State and prove Bernoullis theorem class 11 physics CBSE

The ice floats on water because A solid have lesser class 9 chemistry CBSE

State Newtons formula for the velocity of sound in class 11 physics CBSE